Why can’t higher education agree on terminology for third-space professionals? - Colin Simpson (Journal of Learning Development in Higher Education)
Poorly defined roles and inconsistently used titles present a significant barrier to understanding and valuing the work of third-space professionals (Bird, 2004; Caldwell, 2022; Veles et al., 2023). People in these roles make a significant contribution to learning and teaching in higher education, bringing pedagogical and technological expertise to an increasingly complex domain. A lack of understanding of these roles makes it hard to build trust and foster effective collaboration. This brief communication considers factors in higher education, from the cultural to the pragmatic, which contribute to this confusion.